Pengembangan Modul Ajar Berbasis Lingkungan untuk Meningkatkan Minat Belajar IPA Peserta Didik SMP - Sitti Hadija K. Sidora; Muhammad Arsyad; Husain Husain (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The low level of students' interest in science learning and the limited availability of teaching materials that connect scientific concepts with real environmental contexts have become challenges in the learning process, particularly in areas where local environmental potential has not been optimally utilized. This study aimed to develop an environment-based teaching module for science learning and examine its validity, practicality, and effectiveness in improving students' learning interest at SMPN 1 Talatako. This research employed a Research and Development (R&D) method using the 4D development model consisting of define, design, develop, and disseminate stages. The research sample consisted of 33 seventh-grade students selected through purposive sampling. Data were collected through interviews, expert validation, response questionnaires, and learning interest questionnaires using pretest and posttest procedures. The results showed that the module obtained a material expert validation score of 89.67% and a media expert validation score of 92.36%, both categorized as highly valid. The practicality assessment showed student responses of 88.5% and teacher responses of 90%. The paired sample t-test obtained a significance value of 0.000, while the N-Gain score reached 0.56 in the moderate category. These findings indicate that environment-based teaching modules can create more contextual and engaging science learning experiences. This study concludes that the environment-based teaching module is valid, practical, and effective in improving junior high school students' interest in science learning.